Bittersweet Sugars: How Unusual Glycan Structures May Connect Epithelial-to-Mesenchymal Transition and Multidrug Resistance in Cancer - Leonardo Marques da Fonseca; Israel Diniz-Lima; Marcos André Rodrigues da Costa Santos; Tatiany Nunes Franklim; Kelli Monteiro da Costa; Ariely Costa dos Santos; Alexandre Morrot; Debora Decote-Ricardo; Raphael do Carmo Valente; Celio Geraldo Freire-de-Lima; Jhenifer Santos dos Reis; Leonardo Freire-de-Lima (Medicines, 2023)
Cancer cells are characterized by metabolic reprogramming, which enables their survival in of-ten inhospitable conditions. A very well-documented example that has gained attraction in re-cent years and is already considered a hallmark of transformed cells is the reprogramming of carbohydrate metabolism. Such a feature, in association with the differential expression of en-zymes involved in the biosynthesis of glycoconjugates, generically known as glycosyltransfer-ases, contributes to the expression of structurally atypical glycans when compared to those ex-pressed in healthy tissues. The latest studies have demonstrated that glycophenotypic alterations are capable of modulating multifactorial events essential for the development and/or progres-sion of the disease. Herein, we will address the importance of glycobiology in modern medi-cine, focusing on the ability of unusual/truncated O-linked glycans to modulate two complex and essential phenomena for cancer progression: the acquisition of the multidrug resistance (MDR) phenotype and the activation of molecular pathways associated with the epithelial–mesenchymal transition (EMT) process, an event deeply linked with cancer metastasis.